1992
DOI: 10.1212/wnl.42.5.1029
|View full text |Cite
|
Sign up to set email alerts
|

Protein S deficiency in middle‐aged women with stroke

Abstract: We examined the relationship between free protein S deficiency and cerebrovascular disease by reviewing the records of all patients with the diagnoses of cerebral thrombosis, cerebral embolism, and cerebral vascular occlusion who were referred for coagulation studies over a 12-month period. We assayed for free protein S antigen, protein C antigen, and antithrombin III and tested for lupus-like anticoagulant and anticardiolipin antibody. Twenty-two of 267 patients (8.2%) admitted with thrombotic strokes were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
2
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 0 publications
0
32
2
2
Order By: Relevance
“…More detailed laboratory screening of stroke patients for recently identified prothrombotic states increased the rate of stroke attributed to disturbances of the coagulation system [19, 20, 21, 22, 23, 24, 25, 26, 27, 38]. In ischemic stroke, routine coagulation tests are usually normal, even if they are examined immediately after stroke [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed laboratory screening of stroke patients for recently identified prothrombotic states increased the rate of stroke attributed to disturbances of the coagulation system [19, 20, 21, 22, 23, 24, 25, 26, 27, 38]. In ischemic stroke, routine coagulation tests are usually normal, even if they are examined immediately after stroke [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that the association of a prothrombotic condition with secondary hypercoagulable states (cigarette smoking, pregnancy, puerperium, oral contraceptive use, alcohol consumption, surgery, inflammation, malignancy) may significantly elevate the risk of cerebral ischemia [18]. It has recently been shown that not only venous but arterial thrombosis is also associated with abnormalities of natural coagulation inhibitor activities, and/or decreased fibrinolytic activity [19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…The critical antithrombotic role of protein S is revealed by the massive thrombotic complications suffered by infants homozygous for protein S deficiency. 3 Adult patients with mild heterozygous deficiencies in protein S are associated with risk for venous and arterial thrombosis, 4,5 ischemic stroke, 6 cerebral thrombophlebitis, 7 myocardial infarction, and vascular calcification. 8,9 Protein S infused in a murine model of ischemic stroke decreases infarction and edema volumes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The critical physiological antithrombotic role of protein S is revealed by the massive thrombotic complications suffered by infants homozygous for protein S deficiency. 8,9 In adults, mild heterozygous deficiencies in protein S are associated with risk for venous and arterial thrombosis, 10 -13 ischemic stroke, 14,15 and cerebral thrombophlebitis. 16,17 Protein S binds to vascular cells and is a potent mitogen.…”
mentioning
confidence: 99%